1977
DOI: 10.1037/0022-0663.69.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' attitudinal responses to differing characteristics of elementary school students.

Abstract: This experiment studied attitudinal responses of attachment, rejection, concern, and indifference among 53 elementary teachers as evoked by 16 descriptions of elementary school students differing in four personality characteristics, two levels of academic ability, and sex. A multiple linear regression approach to analysis of variance was used; main and interaction effects of student attributes on teacher attitudes were examined. Main effects for student personality characteristics were found on all four teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

1983
1983
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 4 publications
2
25
0
2
Order By: Relevance
“…Results of this study and of replications by Brooks and Wilson (1978), Brophy and Evertson (1981), Brophy and Good (1974), Good (Note 3), Good and Brophy (1972), Helton and Oakland (1977), Jenkins (Note 4), and Willis and Brophy (1974) are pertinent to the subtle interactions between teachers' attitudes and children's school and sex roles.…”
Section: Teacher Attitudes Toward Children In Their Classroomsmentioning
confidence: 78%
“…Results of this study and of replications by Brooks and Wilson (1978), Brophy and Evertson (1981), Brophy and Good (1974), Good (Note 3), Good and Brophy (1972), Helton and Oakland (1977), Jenkins (Note 4), and Willis and Brophy (1974) are pertinent to the subtle interactions between teachers' attitudes and children's school and sex roles.…”
Section: Teacher Attitudes Toward Children In Their Classroomsmentioning
confidence: 78%
“…He further posited that teachers are more concerned with disruptive types of behaviors because of the institutional demand of conformity, a position also voiced by Silberman (1971). Studies by Feshback (1966) and Helton and Oakland (1977) found higher teacher feelings of attachment for students characterized as rigidconforming-orderly and passive-dependent-acquiescent. Other researchers have found teacher attitudes of indifference toward students who are passive and have low salience in the classroom (Silberman, 1969;Brophy & Good, 1974).…”
Section: Discussionmentioning
confidence: 97%
“…The rest of them denote behavioral difficulties or combinations of difficulties. Helton and Oakland (1977) observed teachers in primary schools -examining their feelings of preference, concern, or rejection with respect to their students. The teachers tended to prefer rigid, conforming, orderly, passive, and dependent children.…”
Section: Children With Learning and Behavioral Difficultiesmentioning
confidence: 99%